2017
DOI: 10.1111/jocs.13206
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Marfans and bicuspid valves on outcomes following aortic valve reimplantation

Abstract: The reimplantation technique for aortic root aneurysms is associated with excellent clinical and functional outcomes at short and mid-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The selection procedure of this systematic review is shown in Figure 1. A total number of 44 studies matched with the inclusion and exclusion criteria and were included for analysis, of which 11 publications separately reported (partially) outcomes on TAV (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and 12 publications on BAV (7,17,20,21,(25)(26)(27)(28)(29)(30)(31)(32). The full list of studies included in this review is presented in the Supplementary material (Appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…The selection procedure of this systematic review is shown in Figure 1. A total number of 44 studies matched with the inclusion and exclusion criteria and were included for analysis, of which 11 publications separately reported (partially) outcomes on TAV (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and 12 publications on BAV (7,17,20,21,(25)(26)(27)(28)(29)(30)(31)(32). The full list of studies included in this review is presented in the Supplementary material (Appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-five percent of patients underwent the David procedure, versus the Yacoub. Of the included papers, nine studies reported freedom from mortality curves ( 14 , 15 , 17 , 18 , 20 , 25 , 27 , 28 ), and 15 studies reported freedom from secondary reoperation curves ( 14 - 21 , 24 - 30 ) amenable to aggregated KM analysis. Six studies were deemed to be of moderate risk of bias, with those remaining as low risk ( 15 - 17 , 24 , 26 , 30 ) (see Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were deemed to be of moderate risk of bias, with those remaining as low risk ( 15 - 17 , 24 , 26 , 30 ) (see Figure S2 ). All studies were determined to be of high quality on quality assessment, with the exception of 5 ( 15 , 18 , 19 , 28 , 30 ) which were deemed of moderate quality. Baseline patient demographic data for medical comorbidities were poorly reported across all included studies, with insufficient data reported for meta-analysis for type 2 diabetes mellitus, hypertension, coronary artery disease, peripheral vascular/arterial disease, chronic obstructive pulmonary disease/emphysema, and smoking history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation